Genetic Ablation of Soluble TNF Does Not Affect Lesion Size and Functional Recovery after Moderate Spinal Cord Injury in Mice - Ditte Gry Ellman; Matilda Degn; Minna Christiansen Lund; Bettina Hjelm Clausen; Hans Gram Novrup; Simon Bertram Flæng; Louise Helskov Jørgensen; Lujitha Suntharalingam; Åsa Fex Svenningsen; Roberta Brambilla; Kate Lykke Lambertsen (Mediators of Inflammation)
Traumatic spinal cord injury (SCI) is followed by an instant increase in expression of the microglial-derived proinflammatory cytokine tumor necrosis factor (TNF) within the lesioned cord. TNF exists both as membrane-anchored TNF (mTNF) and as cleaved soluble TNF (solTNF). We previously demonstrated that epidural administration of a dominant-negative inhibitor of solTNF, XPro1595, to the contused spinal cord resulted in changes in Iba1 protein expression in microglia/macrophages, decreased lesion volume, and improved locomotor function. Here, we extend our studies using mice expressing mTNF, but no solTNF (mTNFΔ/Δ), to study the effect of genetic ablation of solTNF on SCI. We demonstrate that TNF levels were significantly decreased within the lesioned spinal cord 3 days after SCI in mTNFΔ/Δ mice compared to littermates. This decrease did, however, not translate into significant changes in other pro- and anti-inflammatory cytokines (IL-10, IL-1β, IL-6, IL-5, IL-2, CXCL1, CCL2, or CCL5), despite a tendency towards increased IL-10 and decreased IL-1β, TNFR1, and TNFR2 levels in mTNFΔ/Δ mice. In addition, microglial and leukocyte infiltration, activation state (Iba1, CD11b, CD11c, CD45, and MHCII), lesion size, and functional outcome after moderate SCI were comparable between genotypes. Collectively, our data demonstrate that genetic ablation of solTNF does not significantly modulate postlesion outcome after SCI.